2022
DOI: 10.3389/ffunb.2022.837605
|View full text |Cite
|
Sign up to set email alerts
|

Basidiomycota Fungi and ROS: Genomic Perspective on Key Enzymes Involved in Generation and Mitigation of Reactive Oxygen Species

Abstract: Our review includes a genomic survey of a multitude of reactive oxygen species (ROS) related intra- and extracellular enzymes and proteins among fungi of Basidiomycota, following their taxonomic classification within the systematic classes and orders, and focusing on different fungal lifestyles (saprobic, symbiotic, pathogenic). Intra- and extracellular ROS metabolism-involved enzymes (49 different protein families, summing 4170 protein models) were searched as protein encoding genes among 63 genomes selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 159 publications
0
15
0
Order By: Relevance
“…Normally, the KM should not vary much if it was a pure enzyme, but because it is an enzymatic complex, there was a synergism between the intra and extracellular enzymes present. This synergism allowed the potentiation of the complex (Mattila et al, 2022;Bernal et al, 2021;Sakai et al, 2022), obtaining an almost complete degradation of the ICD in the concentration of 50 ppm in 25 days of experimentation, above 90% in Gi2 and above 80% in Gi1 (Table 2).…”
Section: Enzymatic Kinetics Of Extractsmentioning
confidence: 95%
See 2 more Smart Citations
“…Normally, the KM should not vary much if it was a pure enzyme, but because it is an enzymatic complex, there was a synergism between the intra and extracellular enzymes present. This synergism allowed the potentiation of the complex (Mattila et al, 2022;Bernal et al, 2021;Sakai et al, 2022), obtaining an almost complete degradation of the ICD in the concentration of 50 ppm in 25 days of experimentation, above 90% in Gi2 and above 80% in Gi1 (Table 2).…”
Section: Enzymatic Kinetics Of Extractsmentioning
confidence: 95%
“…In shorter periods of growth and WAN (Gi1, 20 days), besides the production of ligninolytic enzymes due to lack of nitrogen, the amount of carbon present stimulates the fungus in the production of intermediate enzymes that degrade other recalcitrant xenobiotic compounds, such as other oxidases producing hydrogen peroxide and intermediate metabolic compounds of low molecular mass (Kaushik & Malik, 2009;Janusz et al, 2017;Mattila et al, 2022;Kenkebashvili et al, 2012;Gupta & Asim, 2019). Therefore, a carbon source mixed with the NL accelerates the bioremediation of the TE (Gupta & Asim, 2019;Davila et al, 2020;Conceição et al, 2017).…”
Section: Phase IImentioning
confidence: 99%
See 1 more Smart Citation
“…The interplay of AA3_2 AADH, GDH, and laccases was also observed, and both AA3_2 AADH and GDH were found to inhibit the formation of laccase-oxidized phenolic products [ 25 , 26 ]. Moreover, a recent genetic study has revealed that large numbers of copies of AA3_2 encoding genes of Basidiomycota fungi co-occur with large numbers of copies of AA2 class II high-redox peroxidases, particularly in white rot and litter decomposing fungi, suggesting a possible role for AA3_2s in lignin oxidation and degradation [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…H 2 O 2 is generated by glucose-methanol-choline oxidoreductases (AA3) and copper radical oxidases (AA5), that target carbohydrate or aliphatic/aromatic alcohols (11,12). In white-rot fungi, H 2 O 2 acts as a co-substrate to fuel different types of LPMOs and AA2 peroxidases (13)(14)(15). While the roles of CAZymes and H 2 O 2 during the degradation of lignocellulose is welldocumented, the impact of ROS on the oxidation of CAZymes remains unclear.…”
Section: Introductionmentioning
confidence: 99%